ARTI PENTING KEBERADAAN SUMBERDAYA MOLUSKA PADA WILAYAH PESISIR: PENDIDIKAN KARAKTER KONSERVASI BAGI GENERASI MUDA - Uneputty, Prulley Annette; Pietersz, Janson Hans; Huliselan, Niette Vuca; Tuapattinaja, Maureen Alise; Tupan, Charlotha Irenny (Universitas Mataram, 2024)
Coastal areas have a relatively high diversity of aquatic organisms, including molluscs. The existence of molluscs has a significant role in maintaining environmental stability and supporting the socio-economic life of coastal communities. Coastal communities on Ambon Island often carry out mollusc utilization activities when seawater is low, which occurs in the morning, afternoon and evening. However, some also do it from evening to early morning. Using these molluscs can cause problems with the diversity and abundance of molluscs and their environmental habitat if carried out with high time intensity and volume of collection and using equipment that is not environmentally friendly. Based on these problems, it is necessary to carry out outreach activities for the younger generation, who are agents of change and successors of the nation, regarding the importance of the existence of mollusc resources in coastal areas for community life and the environment. This outreach activity is also part of the conservation character education that we want to provide from an early age. This activity is carried out through several stages: analyzing the problem and preparing and implementing activities. This service activity was attended by 50 students from class IX junior high school. Community service activities went well, and a very positive response was received from the participants. The success of this activity can also be seen from the participant's responses to the evaluation results before and after the activity, which showed a significant increase in their understanding and knowledge of the counselling material.